Over Our Dead Bodies : Port Arthur and Australia's Fight for Gun Control. - Chapman, Simon (Sydney : Sydney University Press, 2013)
The Port Arthur massacre on 28 April 1996, when 35 people were shot dead by Martin Bryant, transformed Australia's gun control debate. Public outrage drove politicians from all sides of politics to embrace gun control. Non-violent 'people power' galvanised government resolve to outlaw semi-automatic weapons, register all guns and tighten gun ownership laws. Simon Chapman's book gives an insider's view of the struggle for gun control, highlighting the public discourse between shooters determined to preserve the right for civilians to bear military-style weapons, and activists dedicated to getting Australia 'off the American path' of gun violence.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books